2014
DOI: 10.1113/expphysiol.2014.078634
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular acidosis contracts coronary but neither renal nor mesenteric artery via modulation of H+,K+‐ATPase, voltage‐gated K+ channels and L‐type Ca2+ channels

Abstract: New Findings r What is the central question of this study?We asked whether there are any differences in responses to extracellular acidosis among arteries of different origin and whether K + channels, Ca 2+ channels and H + ,K + -ATPase are involved in extracellular acidosis-induced coronary myogenic responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Metabolic acidosis, which is associated with an increased anion gap (infection, intoxication, and lactic acidosis), was also reported to be a common cause of hyperkalemia [ 40 , 43 45 ]. The increased hydrogen ions in the cells might displace potassium from the cells (resulting in an increased serum potassium level) [ 46 48 ]. We suspect that routinely checking the blood pH during the early postresuscitation period would benefit evaluation of the potassium level.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic acidosis, which is associated with an increased anion gap (infection, intoxication, and lactic acidosis), was also reported to be a common cause of hyperkalemia [ 40 , 43 45 ]. The increased hydrogen ions in the cells might displace potassium from the cells (resulting in an increased serum potassium level) [ 46 48 ]. We suspect that routinely checking the blood pH during the early postresuscitation period would benefit evaluation of the potassium level.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, extracellular acidosis was shown to increase arterial tone, as in the aorta and coronary arteries [ 9 , 10 , 11 , 12 ]. However, the prevailing effect of acidosis is the opposite.…”
Section: Acidosis Generally Reduces Tone Of Arterial Vesselsmentioning
confidence: 99%